Annulated heterocyclic derivatives of 1,3,6,8-tetraazapyrene - Martens-Kruck, Susanne; Hahn, Lena; Lombeck, Florian; Rybina, Arina; Wadepohl, Hubert; Gade, Lutz H. (European journal of organic chemistry, 2013)
Polyheterocyclic aromatic compounds combining the electron-poor 1,3,6,8-tetraazapyrene (TAPy) unit with electron-rich heterocycles are reported. They were obtained as side-products from the reaction of the tin “double salt” of tetraaminonaphthalene hydrochloride with trifluoroacetic anhydride in pyridine. Apart from the target product, 2,7-bis(trifluoromethyl)-1,3,6,8-tetraazapyrene (1), several novel heteroaromatics were obtained resulting from the annulation of a furan (2) or indolizine unit (3) to the TAPy core. Upon recrystallization from methanol, methanol added to compound 2 to yield the racemate of the homochiral diastereomer [(R,R)- and (S,S)-2a]. Compound 3 is strongly fluorescent (φ = 0.68 in toluene) and the emission spectra display a significant bathochromic shift with increasing solvent polarity. The HOMO of 3 is located on the indolizine part of the molecule, whereas the LUMO primarily resides on the tetraazapyrene unit, which suggests considerable intramolecular charge transfer in the corresponding π*←π transition.
Gesehen am 23.06.2021